The role of carbon to nitrogen ratio in marron (Cherax cainii, Austin 2002) culture systems - Nguyen, Thi Thu Thuy (Curtin University, 2023)
Carbon to nitrogen (C/N) ratio plays a crucial role in marron aquaculture. This research explored seasonal variations in C/N ratios of sediments in semi-intensive marron ponds. In the indoor laboratory, regular feeding increased nutrient waste accumulation in rearing water but reduced C/N ratios and shifted microbial communities in sediments. Carbohydrate supplementation to marron systems resulted in maintaining water quality, retaining high C/N ratios, enriching bacterial communities in sediments, and improving marron growth and immune performances.